Inflation targeting regimes in the Philippines empirical implications of public debts - Sotocinal, Noli R.
Shows that inflation targeting in the Philippines may be characterized as flexible and adheres to the tenet that its primary focus must be on inflation, although the output gap maybe considered in interest rate setting.